Approaches to Establishing Tolerance in Immune Mediated Diseases - Huffaker, Michelle F.; Sanda, Srinath; Chandran, Sindhu; Chung, Sharon A.; St. Clair, E. William; Nepom, Gerald T.; Smilek, Dawn E. (Frontiers in Immunology, 2021)
The development of rational approaches to restore immune tolerance requires an iterative approach that builds on past success and utilizes new mechanistic insights into immune-mediated pathologies. This article will review concepts that have evolved from the clinical trial experience of the Immune Tolerance Network, with an emphasis on lessons learned from the innovative mechanistic studies conducted for these trials and new strategies under development for induction of tolerance.